Design Science: Approach to Build Design Thinking for Student - Winta Adhitia Guspara (IJCAS (International Journal of Creative and Arts Studies), 2020)
ABSTRACTThe existence of products (artifacts) was not a major element in the design paradigm. Product is like tools to help for designing scenarios, realizing the future, and building design knowledge. Planning and making of a product should have an interconnection between the user, product and environment (e.g. space, social, ecological). Accordingly, three main aspects work on the interconnection of product existence. First is the "action" aspect that the product created when changing user behavior. The second is the aspect of "matter" which talks about functions and purpose to meet user needs. The third is the aspect of "limitation" that arises when every limitation, need, and behavior meets each other. There is one important thing in that discourse, which is how the three aspects (i.e. action, matter, limitation) work and they are interconnected to build of the three design goals (i.e. scenario, future, design knowledge). The fundamental problem for product development was the gap between design theory and design practice. This situation occurs because the development of a product has been moving from the past and present until the future. The issue of conditions and time could not be done through sketches, visual images or also involving tinkering processes involving components and materials. Relied on that, this article invites us to discuss design in a frame of mind called design science. The background of this discussion is an activity, process and design thinking that takes place and address product design students when developing a product. The goals to be achieved through this article is to get compatible design knowledge between the theory (head) and practical aspects (hands). Design Science: Pendekatan untuk Membangun Cara Berpikir Desain bagi Mahasiswa ABSTRAK Keberadaan produk (artifak) bukan merupakan unsur utama dalam paradigma desain. Produk lebih merupakan alat untuk merancang skenario, mewujudkan masa depan, dan membangun pengetahuan desain. Perancangan dan pembuatan sebuah produk harus dapat menghubungkan antara pengguna, produk dan lingkungan (e.g. ruang, sosial, ekologi). Berdasar hal tersebut, terdapat tiga aspek utama yang bekerja pada hubungan keberadaan produk. Pertama yaitu aspek “action” yang ditimbulkan oleh produk ketika merubah perilaku pengguna. Kedua ialah aspek “matter” yang berbicara mengenai fungsi dan tujuan untuk memenuhi kebutuhan pengguna. Ketiga ialah aspek “limitation” yang muncul ketika setiap keterbatasan, kebutuhan, dan perilaku saling bertemu. Terdapat satu perkara penting dalam wacana di atas yaitu bagaimana ketiga aspek (action, matter, limitation) bekerja dan saling terhubung untuk membangun ketiga tujuan desain (skenario, masa depan, pengetahuan desain). Masalah mendasar untuk pengembangan produk adalah kesenjangan antara teori desain dan praktik desain. Situasi ini terjadi karena pengembangan suatu produk bergerak pada masa lalu, sekarang, dan kedepan. Persoalan kondisi dan waktu ini tidak bisa hanya dilakukan melalui sketsa, gambar visual atau juga melibatkan proses utak-atik yang melibatkan komponen dan bahan. Berdasar pada hal itu, maka artikel ini mengajak untuk membahas desain dalam sebuah kerangka pemikiran yang disebut sebagai design science. Latar belakang pembahasan yang digunakan ialah aktivitas, proses dan berpikir desain yang berlangsung pada mahasiswa ketika melakukan pengembangan sebuah produk. Hasil yang ingin dicapai melalui artikel ini ialah mendapatkan pengetahuan desain yang kompatibel antara teori (kepala) dan aspek praktis (tangan).